Primary-Secondary Wavelengths Spectrophotometry to Improve the Direct Determination of Trace Amounts of Volatile Phenol in Wastewater - Gao, Hong-Wen (Asian Journal of Chemistry, 2010)
In alkaline solution and in the presence of potassium ferricyanide the reaction between volatile phenol and 4-aminoantipyrine was applied for the improvement of volatile phenol's detennination in wastewater by primary-secondary wavelengths spectrophotometry (PSWS). Results showed that the analytical precision and accuracy were increased and a higher determination sensitivity was given than that obtained by ordinary spectrophotometry.